PENGEMBANGAN MEDIA SMART READING WITH SCRAPBOOK UNTUK MELATIH KETERAMPILAN MEMBACA SISWA KELAS 1 SEKOLAH DASAR - Anis Solikhah, Siti; Galuh Kartika Dewi; Satrio Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The implementation of learning in schools, especially reading, cannot be separated from learning media. This research was motivated by developing Smart Reading With Scrapbook media to train the reading skills of grade 1 students at SDN Sawocangkring. The aim of this research is to determine students' reading skills after using Smart Reading With Scrapbook media. The research and development method used in this research is the Research and Development (R&D) method, which is research oriented referring to the Borg and Gall model in development and is used to produce a particular product and test the effectiveness of the product. The results of developing the feasibility of the Smart Reading With Scrapbook media based on the media expert's assessment received a score of 86% including the criteria "Appropriate, no need for revision". The material expert's assessment received a score of 85%, including the category "Decent, no need for revision". The final result or average student reading obtained before using the media (pre-test) was 64, while the average score obtained after using the media (post-test) was 92 so that the Ngain score calculation obtained a result of 0.8 in the "High" category. so it is stated in the "Effective" criteria.